2016 Conference for E-Democracy and Open Government (CeDEM) 2016
DOI: 10.1109/cedem.2016.20
|View full text |Cite
|
Sign up to set email alerts
|

Using Open Research Data for Public Policy Making: Opportunities of Virtual Research Environments

Abstract: Abstract-Governments and publicly-funded research organisations increasingly make research data available openly. Researchers can use this data in Virtual Research Environments (VREs) to conduct multidisciplinary data-driven research and to obtain new insights potentially for governmental policy-making. However, the requirements for such a VRE are not yet clear. The objective of this study is to elicit and define requirements for a multidisciplinary VRE that integrates Open Government Data (OGD) and open resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…The implication of the close relationship between OG and OS data is an opportunity to link them more effectively by ICT in order to facilitate scientific data-driven government decisions and policies, scientific discoveries, and innovative public services [28].…”
Section: Fig 7 Relationship Between Os Data and Og Datamentioning
confidence: 99%
“…The implication of the close relationship between OG and OS data is an opportunity to link them more effectively by ICT in order to facilitate scientific data-driven government decisions and policies, scientific discoveries, and innovative public services [28].…”
Section: Fig 7 Relationship Between Os Data and Og Datamentioning
confidence: 99%
“…Some scholars refer to the complete stack of software, data, computing resources, and sensors available to a researcher through a GUI. Others use the term VRE to refer only to an integrating 'hub', composed of a user interface component, a metadata catalogue and an integrating system (e.g., Zuiderwijk et al, 2016). In the second definition the integrating system assembles and provides components which access (via metadata) assets such as datasets, services, software components, workflows, computing facilities and sensors (we call these assets VRE resources).…”
Section: The Vre4eic Reference Architecturementioning
confidence: 99%
“…Maintenance will necessitate resources and processes to accept new user requests, respond to user questions, etc. Prior literature has identified virtual research environments and boundary organizations as key enablers of university-industry collaboration for research data sharing and commercialization (Grayling, 2009;Candela et al, 2013;Perkmann and Schildt, 2015;Zuiderwijk et al, 2016). Both these enablers allow scientists to share their data with stakeholders from academia, government and industry, to integrate datasets and to make new scientific discoveries, potentially leading to open innovation in the form of commercialized new products and services.…”
Section: Generic Framework For Sustainable Business Modelsmentioning
confidence: 99%
“…Prior research has suggested using a virtual research environment (VRE) to foster the transfer of research data from university to industry and its exploitation to generate new data sets, information and knowledge. A VRE acts as an online system, enabling collaborative research activities beyond geographical borders and providing researchers with tools to manage complex tasks (Candela et al, 2013; Grayling, 2009; Zuiderwijk et al, 2016). The online system should have integrated tools for searching, accessing, integrating data and fostering collaboration among researchers (Zuiderwijk et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%